Dynamics of Bimodality in Vehicular Traffic Flows - Mullick, Arjun; Ray, Arnab K. (Journal of Applied Nonlinear Dynamics, 2026)
A model equation has been proposed to describe bimodal features in vehicular traffic flows. The dynamics of the bimodal distribution reveals the existence of a fixed point that is connected to itself by a homoclinic trajectory. The mathematical conditions associated with bimodality have been established. The critical factors necessary for both a breaking of symmetry and a transition from bimodal to uni-modal behaviour, in the manner of a bifurcation, have been analysed.